Long-term exposure to particulate matter and risk of Alzheimer's disease and vascular dementia in Korea: a national population-based Cohort Study - Jung-Im Shim; Garam Byun; Jong-Tae T. Lee (BMC, 2023)
Abstract Background The prevalence of age-related neurodegenerative diseases has risen in conjunction with an increase in life expectancy. Although there is emerging evidence that air pollution might accelerate or worsen dementia progression, studies on Asian regions remains limited. This study aimed to investigate the relationship between long-term exposure to PM10 and the risk of developing Alzheimer's disease and vascular dementia in the elderly population in South Korea. Methods The baseline population was 1.4 million people aged 65 years and above who participated in at least one national health checkup program from the National Health Insurance Service between 2008 and 2009. A nationwide retrospective cohort study was designed, and patients were followed from the date of cohort entry (January 1, 2008) to the date of dementia occurrence, death, moving residence, or the end of the study period (December 31, 2019), whichever came first. Long-term average PM10 exposure variable was constructed from national monitoring data considering time-dependent exposure. Extended Cox proportional hazard models with time-varying exposure were used to estimate hazard ratios (HR) for Alzheimer's disease and vascular dementia. Results A total of 1,436,361 participants were selected, of whom 167,988 were newly diagnosed with dementia (134,811 with Alzheimer's disease and 12,215 with vascular dementia). The results show that for every 10 µg/m3 increase in PM10, the HR was 0.99 (95% CI 0.98-1.00) for Alzheimer's disease and 1.05 (95% CI 1.02-1.08) for vascular dementia. Stratified analysis according to sex and age group showed that the risk of vascular dementia was higher in men and in those under 75 years of age. Conclusion The results found that long-term PM10 exposure was significantly associated with the risk of developing vascular dementia but not with Alzheimer's disease. These findings suggest that the mechanism behind the PM10-dementia relationship could be linked to vascular damage.